2017
DOI: 10.1002/lom3.10214
|View full text |Cite
|
Sign up to set email alerts
|

Water sampling for environmental DNA surveys by using an unmanned aerial vehicle

Abstract: Environmental DNA (eDNA) techniques utilizing DNA fragments from water have recently been developed to investigate the distribution and abundance/biomass of aquatic organisms. The eDNA technique is based on the analysis of DNA fragments in sampled water; thus, an unmanned aerial vehicle (UAV; drone) would be a useful way of collecting water for eDNA sampling, and may consequently allow us to extend eDNA surveys both spatially and temporally. Here, we developed a new method of water collection by using UAV with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Coupling the use of eDNA analyses to advances in marine robotics will usher in a new era for studying ecosystem processes and perhaps provide new ways of collecting biological data that is akin to the physical and chemical sensor data already being collected in the ocean. For example, utilization of drones for eDNA sample collection has been previously reported using an unmanned aerial vehicle (UAV) in a freshwater reservoir (Doi et al, 2017). Hoffmann et al (2016) provides a concept of utilizing a hydroplane drone for improved sample collection with less effort.…”
Section: Autonomous Mobile Sampling Systems For Ednamentioning
confidence: 99%
“…Coupling the use of eDNA analyses to advances in marine robotics will usher in a new era for studying ecosystem processes and perhaps provide new ways of collecting biological data that is akin to the physical and chemical sensor data already being collected in the ocean. For example, utilization of drones for eDNA sample collection has been previously reported using an unmanned aerial vehicle (UAV) in a freshwater reservoir (Doi et al, 2017). Hoffmann et al (2016) provides a concept of utilizing a hydroplane drone for improved sample collection with less effort.…”
Section: Autonomous Mobile Sampling Systems For Ednamentioning
confidence: 99%
“…In this regard, the lakeshore water sampling conducted in the present study revealed the presence of numerous benthopelagic species based on eDNA metabarcoding, but relatively few pelagic species. Accordingly, in order to detect a larger number of pelagic species, we would need to perform offshore sampling, for example, using drone-assisted water collection for eDNA surveys 36 . The lateral body shape traits of species may also be associated with their micro-habitat use; for example, species with eel-like and short and/or deep body shapes appear to prefer sheltered micro-habitats (i.e., beneath stones) and pelagic zones.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the sensitivity of the technique, this is a serious issue in eDNA surveys and may result in false positive detections and subsequent misinterpretation of results (Goldberg et al 2016;Wilson et al 2016). eDNA analysis requires multiple steps of sample handling and manipulation in the field (collection, storage and transportation) and in the lab (storage, DNA extraction, amplification, library preparation and sequencing), so contamination may occur at various stages of the research (Goldberg et al 2016;Doi et al 2017). In the field, contamination may occur when DNA from one or multiple samples is unintentionally transferred into another sample, either from another site in the same study or from an unknown locality.…”
Section: Sample Contaminationmentioning
confidence: 99%